Dizinc lactide polymerization catalysts: Hyperactivity by control of ligand conformation and metallic cooperativity - Thevenon, A; Romain, C; Bennington, M; White, A; Davidson, H; Brooker, S; Williams, C (Wiley, 2016)
Understanding how to moderate and improve catalytic activity is critical to improving degradable polymer production. Here, di- and mono-zinc catalysts, coordinated by bis(imino)diphenylamido ligands, show remarkable activities and allow determination of the factors controlling performance. In most cases, the di-zinc catalysts significantly out-perform the mono-zinc analogues. Further, for the best di-zinc catalyst, the ligand conformation controls activity: the catalyst with ‘folded’ ligand conformations show TOF values up to 60,000 h-1 (0.1 mol% loading, 298 K, [LA] = 1 M), whilst that with a ‘planar’ conformation is much slower, under similar conditions (TOF = 30 h-1). Di-zinc catalysts also perform very well under immortal conditions, showing improved control, and are able to tolerate loadings as low as 0.002 mol% whilst conserving high activity (TOF = 12,500 h-1).